Coherent detection stochastic resonance assisted biomagnetometer for measuring magnetocardiography at room temperature. (27th August 2021) - Liao, Zhiqiang; Jin, Shixu; Kuwahata, Akihiro; Sekino, Masaki; Tabata, Hitoshi
Abstract: A method of magnetocardiography (MCG) measurement using an overdamped bistable model based stochastic resonance (SR) technique for advancing biomagnetic sensors is proposed. To determine the system parameters for SR, an evolutionary algorithm combined with the coherent detection (CD) method is applied. We acquire and process an animal MCG at room temperature, detected by a commercially available optically pumped magnetometer. A comparison with a lowpass filter and the traditional CD method verified the ability of the proposed method to obtain a higher signal-to-noise ratio and peak value of the MCG, whilst retaining sufficient dynamic information.